Rationale and feasibility assessment of an institution‐based virtual reality hub in orthopaedic surgical training: an Australian pilot study. Issue 12 (18th November 2021) - Le, Allan; Krishna, Anuj; Lambers, Anton Philip; Hardidge, Andrew; Balakumar, Jitendra
Abstract: Background: Virtual reality (VR) has been established as a valuable tool outside of medicine but there has been limited uptake in orthopaedics despite being a specialty heavily dependent on psychomotor skills. The purpose of this study was to assess the feasibility of setting up an on‐site virtual reality surgical training hub for an orthopaedic surgery unit. A secondary objective was to document encountered hurdles to assist other institutions with a similar process. Methods: The study explored the logistical and organizational considerations in the process of creating a virtual reality training area. This included: review of location, set up management, funding arrangements, set up time, research opportunities and training time. Set up and completion times were recorded during a separate trial of 24 participants ranging from medical students to senior consultant orthopaedic surgeons. Results: A VR training area was successfully established over a period of 3 months. A dedicated area for training where the equipment remains permanently was designated to facilitate ease of use. Average set up took 7.5 min to turn the computer on and 25 min for the participants to start the module. Issues identified during set up were recorded. Conclusions: The study demonstrated that it is possible to set up a dedicated area for virtual reality surgical training within a hospital unit. A dedicated lockable area is the most feasible method of establishing such a space and reduces the requirement to recalibrate and transfer equipment around the hospital. Abstract : The purpose of this study was to assess the feasibility of setting up an on‐site virtual reality surgical training hub for an orthopaedic surgery unit whilst documenting encountered hurdles. The study demonstrated that it is possible to set up a dedicated area for virtual reality.